Impact of the leaf miner Cameraria ohridella (Lepidoptera: Gracillariidae) and bleeding canker disease on horse‐chestnut: direct effects and interaction. (20th June 2013) - Straw, Nigel A.; Williams, David T.
Abstract The leaf miner Cameraria ohridella and bleeding canker disease (BCD) are invasive organisms causing severe damage to horse‐chestnut trees in Europe. Their impact and potential interaction were investigated by monitoring infestation and disease symptoms on 193 European horse‐chestnuts Aesculus hippocastanum L. and 46 red horse‐chestnuts Aesculus carnea J. Zeyh. over a 10‐year period from 2002 to 2012. Cameraria ohridella damaged up to 75% of the total leaf area of A. hippocastanum, but it had no influence on stem radial growth or general tree condition. Aesculus carnea was rarely attacked and only when growing close to heavily infested A. hippocastanum. BCD, in contrast, was responsible for the death or removal of 11% of A. hippocastanum and 27% of A. carnea, and surviving trees showed a decrease in growth rate and decline in crown density. Cameraria ohridella was more abundant on larger A. hippocastanum, whereas BCD was more prevalent amongst young, fast‐growing A. hippocastanum, which resulted in a partial separation of the moth and disease between trees and habitats, as well as in the wider environment. Trees with higher rates of leaf miner damage generally had a lower incidence of BCD and there was no evidence that C. ohridella either facilitated the spread of the disease or accentuated its impact.